Enhanced quality of electronic clinical record through open-source tool - Nisar, Kashif; Nisar, Saima; Md Said, Abas B (2012)
Electronic records are significant to control healthcare information and save patient lives to increase the value of service in healthcare.This paper is drawn from an ongoing, large-scale research project of implementing an Electronic Clinical Record (ECR).The overall aim in this study is to introduce a new tool for the ECR deeper understanding of the complexities and challenges emerging from the implementation of the ECR, and in particular, to study how to manage a gradual transition to a digital record.The aim is to enable the physician and patient to get access to the electronic clinical record.It will propose a new open-source tool to improve the clinical systems.The objective of this research is to ensure sufficient in-depth knowledge of the challenges confronting service delivery related to health, especially in the healthcare sector; and a grasp of how the underlying ICT infrastructure and an ECR might be expected to assist in meeting these challenges.Results of our study identified the need for more research in this particular area as no definitive solution to the long-term access to electronic clinical records was revealed.Additionally, the research findings highlighted the fact that a few medical institutions may actually be concerned about long-term access to electronic records.